2004
DOI: 10.1111/j.1525-1497.2004.30240.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of bone mineral density testing

Abstract: OBJECTIVES:To identify potential obstacles to bone mineral density (BMD) testing, we performed a structured review of current osteoporosis screening guidelines, studies of BMD testing patterns, and interventions to increase BMD testing. DESIGN:We searched MEDLINE and HealthSTAR from 1992 through 2002 using appropriate search terms. Two authors examined all retrieved articles, and relevant studies were reviewed with a structured data abstraction form. MEASUREMENTS AND MAIN RESULTS:A total of 235 articles were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(18 citation statements)
references
References 75 publications
0
18
0
Order By: Relevance
“…A study of approximately 1,000 women in a single regional health maintenance organization 22 and another in a single academic medical system 23 also found low rates of bone density testing even in patients at high fracture risk. Several studies have found that osteoporosis recognition is low even in patients with fractures 24,25 . Initiation of osteoporosis treatment after fracture was less than 25% in most studies, and empirical treatment (that is, without bone density testing) was even less frequent 26…”
Section: Discussionmentioning
confidence: 99%
“…A study of approximately 1,000 women in a single regional health maintenance organization 22 and another in a single academic medical system 23 also found low rates of bone density testing even in patients at high fracture risk. Several studies have found that osteoporosis recognition is low even in patients with fractures 24,25 . Initiation of osteoporosis treatment after fracture was less than 25% in most studies, and empirical treatment (that is, without bone density testing) was even less frequent 26…”
Section: Discussionmentioning
confidence: 99%
“…One potential explanation for this care gap is the multiple sources of recommendations for BMD testing which do not always agree with the 2010 Canadian CPGs for the diagnosis and management of osteoporosis [ 1 ]. A recent survey of screening for and treatment of osteoporosis identified 24 different sets of published clinical guidelines for BMD testing [ 9 ]. In Ontario, the situation is further confounded by the fact that the current physician fee schedule still refers to the 2002 Canadian CPGs for the diagnosis and management of osteoporosis [ 10 ] which do not emphasize fracture risk or provide clear guidance for referral of high fracture risk patients even though reimbursement policies were changed in 2008 [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the National Ambulatory Medical Care Survey, investigators found that primary care physicians diagnosed osteoporosis in fewer than 2 per cent of women over 60 years old, even though the expected prevalence in this population is 20 to 30 per cent 11 . Men appear to be diagnosed and treated less often than women 12,13 . Several groups have endorsed osteoporosis screening in older adults.…”
Section: Introductionmentioning
confidence: 99%